PENGARUH TATA LETAK PRODUK, HARGA, DAN KERAGAMAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI TOKO BAROKAH TRENGGALEK - Dicki Andrean Sarwono Kusuma; Indah Yuni Astuti; Ririn Wahyu Arida (Cahaya Ilmu Bangsa, 2025)
This research aims to test and explain the influence of product layout, price and product diversity on purchasing decisions at the Barokah Trenggalek Store partially and simultaneously. This research uses quantitative methods and the population studied is all consumers who purchased the Barokah Trenggalek Shop within the 1 month research period. The number of samples taken was 91 respondents, and the sampling method used accidental sampling. Data was collected through questionnaires, while analysis techniques used validity tests, realism tests, classical assumption tests, multiple linear regression analysis, R2 determinant tests, t tests, and f tests. The research results show that (1) the influence of product layout partially has a significant effect on purchasing decisions with a sig. 0.000 < 0.05, (2) price partially has a significant effect on purchasing decisions with a sig value. 0.000 < 0.05, (3) product diversity partially has a significant effect on purchasing decisions with a sig. 0.001 < 0.05, (4) product layout, price and product diversity simultaneously have a significant effect on purchasing decisions with a sig.F value of 0.000 < 0.05. Purchasing decisions at Ayam Toko Barokah Trenggalek are influenced by these three variables amounting to 50.9% while the remaining 49.1% is influenced by other factors outside this research.